An Analysis of Solar Power Plants (PLTS) System as a Power Supply For Submersible Water Pumps - Abdul Hamid; Amani Darma Tarigan; Ahmad Dani (Jurnal Scientia, 2024)
Solar Power Plants (PLTS) are an efficient renewable energy solution for providing electricity, especially in areas not covered by conventional power grids. This study aims to analyze the PLTS system as a power supply for submersible water pumps, focusing on energy efficiency, voltage stability, and system reliability under various operating conditions. The research methodology includes experimental analysis and simulation using a quantitative approach. Data were obtained through direct measurements on a PLTS system consisting of solar panels, a power controller, batteries, and an inverter as the power source for the submersible water pump. The analyzed variables include solar panel output power, battery charging efficiency, and pump performance under different weather conditions and workload scenarios. The results showed that the PLTS system could provide sufficient power to operate the submersible water pump with an average efficiency of XX%. The voltage stability generated by the inverter remained within the appropriate range for pump operation, with minimal fluctuations under maximum load conditions. However, reduced sunlight intensity during cloudy and rainy conditions led to decreased power output, affecting pump performance. To enhance system reliability, it is recommended to use batteries with larger capacity and a smart control system for optimized power distribution. In conclusion, the PLTS system can serve as an effective and environmentally friendly power source for submersible water pumps. However, further optimization is needed to ensure stable performance under various weather conditions.